Education for security of athletics spectacle - Zawartka, Marek (Pedagogiczny wymiar kultury fizycznej i zdrowotnej w życiu współczesnego człowieka, 2016)
Athletics spectacle as a social event of light character, in which both sides of interaction take part – athletes and spectators – could have double nature: positive and negative. What sort of emotions will be evoked at the pitch, depend on correct arrangement of the event, competitors and mostly depend on followers, their culture and behavior habits. Characteristic feature for athletics audience is its division into groups. During the spectacle time, groups occupy the sectors that are appointed by organizers and that area becomes their patch where is accepted by fans behavior style, unity of feelings and reactions. For years during athletics spectacle, there have appeared many symptoms of aggression, racist behaviors, vulgarisms and lack of tolerance for years. In this article it was presented completed education agendas aimed at young followers and also professing norms and values by the groups of pseudo-rooters, during eight years period.